2008
DOI: 10.1007/s10551-007-9657-0
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Female Global Managers: The Role of Mentoring and Networking

Abstract: This paper explores the role of mentoring and networking in the career development of global female managers. The paper is based on data collected from interviews with 50 senior female managers. The voices of the female managers illustrate some of the difficulties associated with informal organisational processes, in particular mentoring and networking, which hinder their career development. The findings confirm that female managers can miss out on global appointments because they lack mentors, role models, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
94
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 39 publications
(47 reference statements)
6
94
1
6
Order By: Relevance
“…Unfortunately, this kind of information is extremely difficult to obtain for significant numbers of individuals. Most studies of social networks in a business context (see Linehan and Scullion, 2008;Metz and Tharenou, 2001;Tattersall and Keogh, 2006;Forret and Dougherty, 2004) have conducted interviews and collected detailed information about a relatively small number of individuals and their active networks of contacts; these subjects are often employees of the same firm or users of the same professional network (which raises questions about selection). We do not have such data.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Unfortunately, this kind of information is extremely difficult to obtain for significant numbers of individuals. Most studies of social networks in a business context (see Linehan and Scullion, 2008;Metz and Tharenou, 2001;Tattersall and Keogh, 2006;Forret and Dougherty, 2004) have conducted interviews and collected detailed information about a relatively small number of individuals and their active networks of contacts; these subjects are often employees of the same firm or users of the same professional network (which raises questions about selection). We do not have such data.…”
Section: Data Descriptionmentioning
confidence: 99%
“…In organizational settings, a network usually involves contacts with a variety of colleagues for the purpose of mutual work benefits (Linehan and Scullion, 2008). It also depends on informal interactions involving favors, persuasion, and connections to people who already have influence 33 4…”
Section: Understanding Network In Organizationsmentioning
confidence: 99%
“…Organizational networks influence promotion and acceptance, particularly of female employees Linehan and Scullion (2008). Their findings also revealed that effective networking is a key barrier to the …”
Section: Female Media Workers' Employment Status: Demographic Andmentioning
confidence: 95%